1999
DOI: 10.1200/jco.1999.17.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Magnetic Resonance Imaging in the Management of Breast Cancer: Evidence for Improved Preoperative Staging

Abstract: By applying MRI selectively to patients with a known diagnosis of cancer and focusing on defining the extent of malignant lesions, we were able to obtain clear and accurate anatomic information. Our results suggest that MRI could provide very valuable information for preoperative planning and single-stage resection in breast cancer. Based on preliminary data from our series, MRI would be valuable as a staging tool in the preoperative setting even if the cost is in the range of $1,300 to $2,000. It is already s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
197
1
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(212 citation statements)
references
References 23 publications
3
197
1
11
Order By: Relevance
“…This is in contrast to previous reports, which found correlation coefficients ranging from 0.70 to 0.98 for MRI (Esserman et al, 1999;Partridge et al, 2002;Rosen et al, 2003;Wasser et al, 2003;Martincich et al, 2004). However, a recent retrospective review of neoadjuvant chemotherapy trials from the MD Anderson Cancer Center also found a poor agreement between tumour size measurements by mammography or ultrasound and histopathology (Chagpar et al, 2006).…”
Section: Discussioncontrasting
confidence: 54%
“…This is in contrast to previous reports, which found correlation coefficients ranging from 0.70 to 0.98 for MRI (Esserman et al, 1999;Partridge et al, 2002;Rosen et al, 2003;Wasser et al, 2003;Martincich et al, 2004). However, a recent retrospective review of neoadjuvant chemotherapy trials from the MD Anderson Cancer Center also found a poor agreement between tumour size measurements by mammography or ultrasound and histopathology (Chagpar et al, 2006).…”
Section: Discussioncontrasting
confidence: 54%
“…Magnetic resonance imaging has been shown to correspond better with pathological size measurement than XRM (Esserman et al, 1999;Drew et al, 2001) and to be less obscured by dense breast diseases. Ultrasound measurement is more accurate than XRM, but fails when the tumour to be measured is larger than the field of view or complex in shape.…”
mentioning
confidence: 99%
“…Widespread detection thanks to mammography and ultrasound allows earlier detection of cancer and has been shown to improve the survival of women with breast cancer (25,26). Early detection of breast cancer allows also conservative surgery as an alternative to mastectomy (27,28). However, breast lesions remain difficult to diagnose and characterize, especially in dense fibroglandular breasts.…”
Section: Discussionmentioning
confidence: 99%